Activity test of antibacters combinations of avocado leaf extract (persea americana) and papaya leaf (carica papaya l.) against the growth of eschericia coli atcc 25922 - More, Evanisia; Mandala, Fitria Mentari; Turwewi, Serlibrina Wulandari (Institute Of Computer Science (IOCS), 2025)
The purpose of this research is to find out whether extracts from avocado and papaya leaves can suppress the growth of the Eschericia coli ATCC 25922 bacterium. This study used a post-test-only control group design, which is typical of genuine experiments. The antibacterial activity of avocado leaf and papaya leaf extracts was tested using the well diffusion method. The concentration ratios of the extracts were 25%:75%, 50%:50%, and 75%:25%. The growth of Eschericia coli ATCC 25922 was used as a positive control, and aquadest as a negative control. The inhibition zone data was analyzed using the one way anova test. Both extracts tested positive for flavonoids, alkaloids, tannins, and saponins, according to this study. The average diameter of the inhibition zone was 15.99 mm, 18.44 mm, and 24.36 mm, respectively, when the concentration ratio was 25%:75%, 50%:50%, and 75%: 25%. On average, the positive control group's inhibition zone measured 27.79 mm in diameter. A one-way ANOVA test revealed a significant difference between all treatments and the positive control group (p=0.000, sig.<0.05). Findings indicate that a 75%:25% mixture of avocado and papaya leaf extracts, with a very strong category, has the most effective antibacterial action.